Effects of a Salty Reduction Program in the Suspected Hypertensive Patients in Health Area 7 - ตฤณวุฒิพงษ์, กรรณิการ์; Rachagrai, Thipaporn; Tumala, Prapasi; Nasa-arn, Som (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2021)
This study was a quasi-experimental research that aimed to assess the effects of the salinity reduction program in suspected hypertensive patients in health region 7. The study was conducted between December 2018 and July 2019, using a participatory learning process which consisted of providing advice, consultation, and exchanging techniques for reducing salt and sodium intake. District sampling was conducted in 50 percent of the 77 districts. One community per district was randomly assigned, then a simple random sampling of 50 suspected hypertensive patients, totaling 1,903 persons. Data was collected by means of knowledge assessment, physical examination, and food salinity measurement. Data was evaluated at month 0, 1 and 2, and the data were analyzed by descriptive and inferential statistics to compare the knowledge, sodium, salt, and blood pressure before and after with Paired t-test statistics. Comparisons were made of blood pressure before and after proceeding with Stuart-Maxwell test, with the statistical significance level of 0.05. The results showed that knowledge score was increased significantly (Mean difference = 3.13; 95% CI: 3.03–3.24, p-value < 0.001). The dietary sodium after the study, the mean was 305.05 mg (SD = 115.89), was lower significantly (Mean difference = 94.99; 95% CI: 90.08–99.90, p-value < 0.001). The proportion of blood pressure levels before and after being significantly different at the 0.05 level (Stuart-Maxwell Chi-square = 592.78, p-value < 0.001). Assessment of dietary salinity and blood pressure monitoring at home in suspected hypertensive patients can raise awareness of the benefits of reducing salt consumption, including lowering blood pressure and lowering the possibility of related coronary diseases. Health literacy of the effects of high salt and sodium consumption should be encouraged. The study sample is a good model for expanding the at-risk group in the community and to encourage public policy for reducing salinity, disease, and increasing health benefits in a sustainable manner.